Comparative Study of Thermochemical Properties of Fluorographene at Different Temperatures: A Computational Approach - Sam1, Linu; Suba2, K.; Amrutha1, R. (Asian Journal of Chemistry, 2013)
Extraordinary properties of graphene continue to attract intense interest that has expanded into research areas. One of the research directions that have emerged recently is based on the notion of graphene being a giant macromolecule, which as any other molecule can be modified in chemical reactions. Graphene's surface has been decorated with various atoms. One way to create more stable graphene derivatives is to try using agents that bind to carbon stronger than hydrogen. Fluorine is one such candidate. Fluorographene is, in a simplified way, a 2D version of Teflon/PTFE which consists of long 1D poly(tetrafluoroethene) polymer molecules. Like poly(tetrafluoroethene) (PTFE), fluorographene has a high thermal stability and excellent 'non-stick' properties. Also like poly(tetrafluoroethene), it is chemically very stable, i.e. very inert, so, combined with its great thermal stability, it can be used as a stable surfacing material over a wide temperature range. In this paper, fluorographene is optimized using Gaussian 03. Fluorographene's thermochemical properties are analyzed over a range of temperatures. The ionization potential is also analyzed and compared to graphene.